Performance of Coconut Hybrids in United Plantations Berhad and Commercial Production of Seed Nuts - Arulandoo, Xaviar; Sritharan, Kandha; Subramaniam, Mohan (International Coconut Community Journal, 2014)
United Plantations Berhad began its first coconut planting in 1912. Since then, it has been the responsibility of the breeding team in its research department to sustain a high standard of plant breeding techniques in the development of future planting materials aligned with the objectives of the company. The yield performance of Tall x Tall, Dwarf x Dwarf and Dwarf x Tall hybrids as well as salient points in the commercial production of hybrid seed nut is highlighted. Current plantings at UPB consist of older generation of MAWA+ with average yields of 30,000 nuts per hectare per year and newer generations of MATAG* with yields comparable to MAWA but with improved nut characteristics. Breeding strategies are now in place to produce hybrids (Dwarf x Tall) capable of out-performing the MATAG in terms of yield and nut characteristics with minimum yields per hectare of 40,000 nuts and eight tonnes copra. Amongst the Tall x Tall hybrids and pure lines of Tall, highest yields were achieved with Tagnanan followed by West African with yields of 24,190 and 23,514 nuts per hectare, respectively, adopting a planting density of 178 palms per hectare. The highest yielding Dwarf x Dwarf cross and self is the Aromatic Green (AGD) and CAMMA++, which provided a similar yield magnitude of 40,000 nuts per hectare planted at a density of 265 palms per hectare. However, as they had lower copra yield as dry nut and lower water content as fresh nut, Dwarf x Dwarf was not the desired commercial planting material. Hence, the breeding programme emphasized in the creation of Dwarf x Tall hybrids aimed at exploiting the large nut size from the tall and high nut number from the dwarf. Amongst the hybrids evaluated in UPB, MATAG hybrid though with lower nut yields had 53.9% higher copra yields per hectare than both AGD and CAMMA making it at present the preferable choice for commercial planting. Newer hybrids are currently being evaluated which shows promise of similar nut yield but improved nut characteristics. The commercial seednut production field is confined to a block of 25 hectares and is operated by the Research Department with a maximum production capacity of 110,000 saleable hybrid seednuts (4 months old) germinated seednuts per year. With escalation in costs of inputs and wages, the cost of seednut production has risen to RM30 per seednut in 2014. However, with good agricultural management practices complementing the superior hybrid planting materials, the production cost of a mature coconut from the plantations is relatively low, thus ensuring a sustained profitability of the coconut plantations in United Plantations Berhad.